Evolving Radiotherapy Techniques in Paediatric Oncology. Issue 3 (March 2019) - Steinmeier, T.; Schulze Schleithoff, S.; Timmermann, B.
Abstract: Aims: Childhood cancer is rare and survival of childhood cancer has increased up to 80% at 5 years after diagnosis. Radiotherapy is an important element of the multimodal treatment concept. However, due to growing tissue, children are particularly sensitive to radiation-related side-effects and the induction of secondary malignancies. However, radiotherapy techniques have continuously progressed. In addition, modern treatment concepts have been improved in order to minimise long-term effects. Today, radiotherapy is used for various tumour types in childhood, such as sarcomas and tumours of the central nervous system. Materials and methods: External beam therapy with either photons or protons and brachytherapy are predominantly used for the treatment of childhood tumours. Technical developments and features, as well as clinical outcomes, for several tumour entities are presented. Results: The development of radiotherapy techniques, as well as risk-adapted therapy concepts, resulted in promising outcome regarding tumour control, survival and therapy-related side-effects. It is assumed that proton therapy will be increasingly used for treating children in the future. However, more data have to be collected through multi-institutional registries in order to strengthen the evidence. Conclusion: The development of radiotherapy techniques is beneficial for children in terms of reducing dose exposure. As compared with other modern and highly conformal techniques, particularly proton therapy may achieve high survival rates and tumour control rates while decreasing the risk for side-effects. However, clinical evidence for modern radiotherapy techniques is still limited today. An optimal patient triaging with the selection of the most appropriate radiation technique for each individual patient will be an important goal for the future.